Transcriptome profile of highly osteoblastic/cementoblastic periodontal ligament cell clones - Miki Taketomi SAITO; Luciana Souto MOFATTO; Mayra Laino ALBIERO; Márcio Zafallon CASATI; Enilson Antonio SALLUM; Francisco Humberto NOCITI JUNIOR; Karina Gonzales SILVÉRIO (University of São Paulo, 2020)
Abstract Heterogeneous cell populations of osteo/cementoblastic (O/C) or fibroblastic phenotypes constitute the periodontal dental ligament (PDL). A better understanding of these PDL cell subpopulations is essential to propose regenerative approaches based on a sound biological rationale. Objective Our study aimed to clarify the differential transcriptome profile of PDL cells poised to differentiate into the O/C cell lineage. Methodology To characterize periodontal-derived cells with distinct differentiation capacities, single-cell-derived clones were isolated from adult human PDL progenitor cells and their potential to differentiate into osteo/cementoblastic (O/C) phenotype (C-O clones) or fibroblastic phenotype (C-F clones) was assessed in vitro. The transcriptome profile of the clonal cell lines in standard medium cultivation was evaluated using next-generation sequencing technology (RNA-seq). Over 230 differentially expressed genes (DEG) were identified, in which C-O clones showed a higher number of upregulated genes (193) and 42 downregulated genes. Results The upregulated genes were associated with the Cadherin and Wnt signaling pathways as well as annotated biological processes, including "anatomical structure development" and "cell adhesion." Both transcriptome and RT-qPCR showed up-regulation of WNT2, WNT16, and WIF1 in C-O clones. Conclusions This comprehensive transcriptomic assessment of human PDL progenitor cells revealed that expression of transcripts related to the biological process "anatomical structure development," Cadherin signaling, and Wnt signaling can identify PDL cells with a higher potential to commit to the O/C phenotype. A better understanding of these pathways and their function in O/C differentiation will help to improve protocols for periodontal regenerative therapies.